Efficient low-grade heat harvesting enabled by tuning the hydration entropy in an electrochemical system - Gao, Caitian (2022)
Harvesting of low-grade heat (<100 °C) is promising, but its application is hampered by a lack of efficient and low-cost systems. The thermally regenerative electrochemical cycle (TREC) is a potential alternative system with high energy-conversion efficiency. Here, the temperature coefficient (α), which is a key factor in a TREC, is studied by tuning the hydration entropy of the electrochemical reaction. The change of α in copper hexacyanoferrate (CuHCFe) with intercalation of different monovalent cations (Na+ , K+ , Rb+ , and Cs+ ) and a larger α value of -1.004 mV K-1 being found in the Rb+ system are observed. With a view to practical application, a full cell is constructed for low-grade heat harvesting. The resultant ηe is 4.34% when TREC operates between 10 and 50 °C, which further reaches 6.21% when 50% heat recuperation is considered. This efficiency equals to 50% of the Carnot efficiency, which is thought to be the highest ηe reported for low-grade heat harvesting systems. This study provides a fundamental understanding of the mechanisms governing the TREC, and the demonstrated efficient system paves the way for low-grade heat harvesting.